Lesiones dentarias cervicales inducidas por oclusión traumática - Gerardo Becerra-Santos (Universidad de Antioquia, 1998)
Some studies had supported the theory that stress concentration in the cervical area of the teeth is responsible not only for the development of dental cervical lesions but also for restorations retention failures. This article establishes the appropriate terminology for the different non- carious dental cervical lesions and describes those related with the occlusal trauma.